COUNSELING AND ASSISTANCE ON THE PROCEDURE FOR MAKING NIB AND PAYMENT USING QRIS - Dian Novianti; Suhana Minah Jaya; Sokid Sokid; Pahla Widyani; devi yuliananda; Fitri Dian Perwitasari (Jurnal Abdisci, 2025)
Background. The Business Identification Number (NIB) is a licensing identity that must be owned by business actors to ensure the legality of their business. On the other hand, the digitization of the payment system is growing with the presence of QRIS (Quick Response Code Indonesian Standard), which facilitates non-cash transactions quickly and efficiently. Aims. This community service activity aims to provide counseling on the procedure for making NIB and using QRIS for micro and small businesses (MSMEs) in Lingsana Village, Jalaksana District, Kuningan Regency. Methods. The method used is direct counseling through lectures, discussions, and practical simulations. Based on pre-test and post-test evaluations, participants consisting of 30 MSME actors showed an increase in understanding by 85%. Result. The results of this activity are expected to encourage business formalization and adoption of digital payment technology among MSMEs. Conclusion. NIB and MSME actors get legal protection, better access to capital, and empowerment from the government. Implementation. This program is expected to encourage local economic growth by strengthening the position of MSMEs in the digital era.